Semantic and Structural Image Segmentation for Prosthetic Vision - Sanchez Garcia, Melani; Martínez Cantín, Rubén; Guerrero, José J. (Jornada de Jóvenes Investigadores del I3A, 2019)
We present a new approach to build a schematic representation of indoor environments for phosphene images. The proposed method combines a variety of convolutional neural networks for extracting and conveying relevant information about the scene such as structural informative edges of the environment and silhouettes of segmented objects. Experiments were conducted with normal sighted subjects with a Simulated Prosthetic Vision system.